2018
DOI: 10.1002/cphc.201701273
|View full text |Cite
|
Sign up to set email alerts
|

Long Periodic Structure of a Room‐Temperature Ionic Liquid by High‐Pressure Small‐Angle X‐Ray Scattering and Wide‐Angle X‐Ray Scattering: 1‐Decyl‐3‐Methylimidazolium Chloride

Abstract: The Bragg reflections of 1-decyl-3-methylimidazolium chloride ([C mim][Cl]), a room-temperature ionic liquid, are observed in a lowly scattered wavevector (q) region using high-pressure (HP) small-angle X-ray scattering methods. The HP crystal of [C mim][Cl] was characterized by an extremely long periodic structure. The peak position at the lowest q (1.4 nm ) was different from that of the prepeak observed in the liquid state (2.3 nm ). Simultaneously, Bragg reflections at high-q were detected using HP wide-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…In addition to temperature changes, effects of other external constraints, such as pressure, shear flow, and electric field, , on microstructural and dynamical heterogeneities of bulk ILs have been investigated via numerous experimental and computational studies. Imidazolium ILs consisting of either small halides (Cl, , Br), [BF 4 ], , [PF 6 ], , or [NTF 2 ] anions , exhibit complicated phase behaviors due to conformational flexibilities of alkyl chains. The external constraints can significantly affect conformational equilibrium of imidazolium cations and anions, like [NTF 2 ], ,, which directly contribute to distinct IL structural transitions.…”
Section: Pure Ionic Liquidsmentioning
confidence: 99%
“…In addition to temperature changes, effects of other external constraints, such as pressure, shear flow, and electric field, , on microstructural and dynamical heterogeneities of bulk ILs have been investigated via numerous experimental and computational studies. Imidazolium ILs consisting of either small halides (Cl, , Br), [BF 4 ], , [PF 6 ], , or [NTF 2 ] anions , exhibit complicated phase behaviors due to conformational flexibilities of alkyl chains. The external constraints can significantly affect conformational equilibrium of imidazolium cations and anions, like [NTF 2 ], ,, which directly contribute to distinct IL structural transitions.…”
Section: Pure Ionic Liquidsmentioning
confidence: 99%
“…酸 化 物 イ オ ン 伝 導 体 は 固 体 酸 化 物 形 燃 料 電 池 等 へ 応 用 さ れ 、性 能 の 向 上 に は よ り 高 い 酸 化 物 イ オ ン 伝 導 度 を 持 つ 物 質 を 発 見 す る こ と が 重 要 で あ る 。酸 化 物 イ オ ン 伝 導 度 は 結 晶 構 造 と 密 接 な 関 係 が あ り 、高 い 酸 化 物 イ オ ン 伝 導 度 を 持 つ 構 造 と し て <111>層 状 ペ ロ ブ ス カ イ ト 構 造 が 挙 げ ら れ る [1] [2 ] 。 本 研 究 で は 高 い イ オ ン 伝 導 度 を 持 つ こ と が 報 告 さ れ て い る Ba7Nb4MoO20 に 注 目 し た [3] 。 Ba7Nb4MoO20 に お け る Nb の 一 部 を 価 数 の 大 き い カ チ オ ン M で 置 換 し イ オ ン 伝 導 度 の 向 上 を 狙 い 、さ ら に 向 上 し た 伝 導 度 の 要 因 を 結 晶 構 造 解 析 か ら 調 べ た 。 化 合 物 Ba7Nb4−xMxMoO20+x/2 を 固 相 反 応 法 で 合 成 し た 。 合 成 し た 化 合 物 に つ い て 、XRD 測 定 に よ り サ ン プ ル の 合 成 を 確 認 し た 後 、全 電 気 伝 導 度 と バ ル ク 伝 導 度 を 測 定 し た 。 カ チ オ ン 置 換 量 x の 値 を 0→0.1→0.2 と 増 加 さ せ る と 伝 導 度 が 増 加 し 、 x = 0.2 の Ba7Nb3.8M0.2MoO20.1 は 実 用 材 料 の YSZ (Zr0.85Y0.15O1.93)よ り 300℃で 約 200 倍 高 い バ ル ク 伝 導 度 を 持 つ こ と を 発 見 し た 。 さ ら に 、 Ba7Nb3.8M0.2MoO20.1 の 酸 化 物 イ オ ン 輸 率 は 600℃ 以 上 で 1 に 近 か っ た 。 Ba7Nb4−xMxMoO20+x/2 (x = 0, 0.1, 0.2)に つ い て 、Echidna (ANSTO), SuperHRPD (J-PARC)で 高 温 中 性 子 回 折 測 定 を 行 い 、 測 定 デ ー タ を リ ー ト ベ ル ト 解 析 (RIETAN-FP, Z-code)に よ っ て 結 晶 構 造 解 析 を 行 っ た 。 解 析 の 結 果 、 800℃に お い て ab 面 上 で の 格 子 間 酸 素 O5 の 占 有 率 に 変 化 が 見 ら れ た 。x の 値 が 0→ 0.1→ 0.2 と 増 加 す る と 、 O5 の 占 有 率 は 0.037(2)→ 0.053(1)→ 0.071(15)と 増 加 し て い る こ と が 分 か っ た 。x の 値 の 増 加 に 伴 っ て 、 伝 導 度 の 向 上 と 格 子 間 酸 素 O5 の 増 加 が 確 認 さ れ た こ と か ら 、 伝 導 度 と 占 有 率 と の 関 係 性 が 明 ら か に な っ た 。 さ ら に 、 結 合 原 子 価 法 (BVE 法 ) に 基 づ い て 酸 化 物 イ オ ン の 拡 散 経 路 を 計 算 し た と こ ろ 、 ab 面 上 で の 二 次 元 的 拡 散 を し て い る と 分 か っ た 。…”
Section: Oa-i-02unclassified
“…The presence of intramolecular kinks and curls in C 7 O 3 mim + /NTf 2 – show that this liquid is denser and show less response to high pressures . High-pressure small-angle X-ray methods were used to calculate the Bragg reflections of 1-decyl-3-methylimidazolium chloride . The low- q -peaks of the liquid state and the solid state are different, and the authors observed the phase transition with the increasing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…36 High-pressure small-angle X-ray methods were used to calculate the Bragg reflections of 1-decyl-3-methylimidazolium chloride. 62 The low-q-peaks of the liquid state and the solid state are different, and the authors observed the phase transition with the increasing pressure. Raman spectroscopy, single-crystal X-ray diffraction (XRD), and optical microscopy methods were used to probe the polymorphic behavior of IL, 1-butyl-3-methylimidazolium hexafluorophosphate [bmim][ PF 6 ].…”
Section: Introductionmentioning
confidence: 99%